Mechanical engineer's solutions suite machine design, metalworking - Hicks, Tyler Gregory; McGraw-Hill Book Company ([New York] : McGraw-Hill, 1998)
An electronic rendering of selections from Standard handbook of engineering calculations, 3rd ed., by Tyler G. Hicks, this package calculates answers to applied machine design and metalworking problems. Includes more than 130 live math formulas and equations.
System requirements: System requirements: PC with 486 or higher processor; MS Windows 3.1, Windows 95 or Windows NT 3.51 or later; 16MB RAM; 10MB available hard disk space; SVGA monitor; 2x CD-ROM drive; mouse.
Keywords: Engineering mathematics; Machine design -- Problems, exercises, etc; Metal-work -- Problems, exercises, etc